SISTEM MEDIASI DALAM PERADILAN ADAT ACEH - Nurdin , Mulyadi (IAIN LANGSA, 2019)
Adat as a traditional justice system, is one way to resolve disputes in the communitypeacefully ou tside the court, through a process of mediation or peace. The tradition which isIndonesian wisdom continues to live and develop. But in its implementation it often facesvarious problems, suchas, obstacles to the recognition of customary court decisions by lawenforcement, as well as synchronization between judicial institutions. The mediation systemthrough customary justice if properly functioned, will solve various problems quickly, cheaplyand fairly. Various problems that occur, related to customary justice, can be resolved, if there aregood wishes between state institutions